Faktor-faktor yang Mempengaruhi Penggunaan Application-based Short Distance Delivery Service. - Purnamaningsih .; Trihadi Pudiawan Erhan; Nosica Rizkalla (Universitas Multimedia Nusantara, 2018)
Abstract The development of e-commerce in Indonesia these days are not only came from the contribution of technology giants such as Zalora and Berry Benka, but also the growth of small scale online shop that utilize e-marketplace like Tokopedia and Bukalapak and social media. As this sector grew, another business that also flourish in this situation is the application based short distance delivery services. Although viewed to simplify the process of order delivery, not all online shop has fully adopted this app yet. It was suspected that the unavailability of service standard and price plays a major role in this situation. This research is conducted to investigate the variables that determines the consumer behavior regarding the usage of the short distance delivery application. The analysis is carried out by using the Structural Equation Modeling method with Lisrel 8.8 to examine 4 hypotheses. The result shows that the factor that encourage customer to repeatedly use this kind of application is whether or not the applications are useful to them. Other than that, price value also impacts the customer behavior. This then lead to the race between those application to give the most competitive price possible Key Word: Behavioral Intention, Performance Expectancy, Effort Expectancy, dan Price Value